Juridical Analysis of Music Uploaded on Tiktok Media in View of Intellectual Property Law - Deni Admadja (International Asia Of Law and Money Laundering, 2022)
The use of technology, especially the internet today shows tremendous development. Almost all people use social media as a container or their means of communication or just expressing themselves. There are so many types of social media currently available in Indonesia. One of the social media available in Indonesia and currently also experiencing significant developments and trends is Tiktok social media. The form of Tiktok social media in the form of these videos, often when users create Tiktok videos it uses songs as the background sound of the video. This research will discuss about how the legal protection of Tiktok application users against copyright holders of songs uploaded on Tiktok? How to resolve disputes if there are legal problems? This study uses normative juridical research methods with secondary data. Based on the results of the study, it was concluded that there is a form of legal protection of TikTok application users against copyright holders for songs uploaded on Tiktok, including in the form of a cooperation agreement contained in User Generated Content. Of course, this form of legal protection is based on the provisions of applicable laws and regulations in the form of special rules for musical works and recording artists that are part of Intellectual Property Rights.